A Radical Chain: Mononuclear "Gold Only" Photocatalysis. Issue 3 (2nd December 2021) - Witzel, Sina; Hoffmann, Marvin; Rudolph, Matthias; Rominger, Frank; Dreuw, Andreas; Hashmi, A. Stephen K.
Abstract: We herein report an unprecedented reactivity of mononuclear gold catalysts acting as classical catalysts and at the same time as active partners in a radical chain mechanism, whereby gold is the only catalyst. The mechanism of the photo‐induced photosensitizer‐free "gold only"‐catalyzed cross coupling was studied in detail – experimentally and theoretically – based on the reaction between arylboronic acids and aryldiazonium salts. With a systematic set of stoichiometric experiments under various conditions and analytic methods, we could show that this mechanism is initiated by an aryl radical formed in the presence of blue LEDs and MeOH. This aryl radical enters the catalytic cycle to oxidize gold(I) to gold(II). Single electron transfer from gold(II) to the aryldiazonium salt then gives the cationic gold(III) complex by formation of a chain‐supporting aryl radical which then is enabled to start a new cycle by oxidation of gold(I) without the need for irradiation. At least every 432 cycles of the radical chain, a new chain‐initiating radical has to restart the radical chain. Eventually, the boronic acid is activated by the BF4 − anion to transmetalate to gold(III), and reductive elimination delivers the desired product. Abstract :